Stepwise wiring of the Drosophila olfactory map requires specific Plexin B levels. - Li, J.; Guajardo, R.; Xu, C.; Wu, B.; Li, H.; Li, T.; Luginbuhl, D.J.; Xie, X.; Luo, L. (eLife, 2018)
The precise assembly of a neural circuit involves many consecutive steps. The conflict between a limited number of wiring molecules and the complexity of the neural network impels each molecule to execute multiple functions at different steps. Here, we examined the cell-type specific distribution of endogenous levels of axon guidance receptor Plexin B (PlexB) in the developing antennal lobe, the first olfactory processing center in Drosophila. We found that different classes of olfactory receptor neurons (ORNs) express PlexB at different levels in two wiring steps - axonal trajectory choice and subsequent target selection. In line with its temporally distinct patterns, the proper levels of PlexB control both steps in succession. Genetic interactions further revealed that the effect of high-level PlexB is antagonized by its canonical partner Sema2b. Thus, PlexB plays a multifaceted role in instructing the assembly of the Drosophila olfactory circuit through temporally-regulated expression patterns and expression level-dependent effects.